Development Behavior for Post-Tensioned Self-Centering Steel Connection under Cyclic Loading - Ahmadreza Torabipour; M. R. Shiravand (Salehan Institute of Higher Education, 2017)
One of the newest steel beam-column joints to replace conventional welded connections, post-tensioned connection steel is with the upper and lower angles. In this connection are high-strength steel strands that parallel beam web and angles between beams and column. Actually high resistance strands and upper and lower angles respectively are provider centralization properties and energy dissipation capacity of the connection. The benefits of post-tensioned steel can be used in connection with the centralization and lack of relative displacement (drift) persistent, stay elastic core components such as connecting beams, columns and fountains connection, appropriate initial stiffness and joint manufacture with materials and traditional skills. . In this study, numerical modelling in Abaqus software, the results of the analysis were compared with the results of laboratory samples and the results showed that the two together are a perfect match. After validation, parameters influential centrist connection then pulled the thick angles in three numerical models were evaluated. The results show that by increasing the thickness of the angles, increase energy dissipation capacity and ductility connection and the β₁ value does not experience tangible changes with changes in angle thickness.